Meridional heat transport variability induced by mesoscale processes in the subpolar North Atlantic - Jian Zhao (Nature Portfolio, 2018)
The oceanic heat transport is traditionally believed to be determined by the large-scale ocean circulation. New findings suggest that the energetic mesoscale processes in the Iceland Basin profoundly modulate the oceanic heat transport variability on time scales from intra-seasonal to interannual.